2021
DOI: 10.1186/s12944-021-01486-w
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter arterial chemoembolization combined with Hippo/YAP inhibition significantly improve the survival of rats with transplanted hepatocellular carcinoma

Abstract: Background This study aimed to explore the effect of inhibiting the Hippo/Yes-associated protein (YAP) signaling pathway on the outcomes of transcatheter arterial chemoembolization (TACE) in treating transplanted hepatocellular carcinoma (HCC). Methods A transplanted HCC rat model was established. Then, rats were randomly divided into four groups: Sham, TACE, verteporfin (inhibitor of Hippo/YAP), and TACE+verteporfin. Lent-OE-YAP was transfected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Therefore, our result suggested that verteporfin could be used as a preventive drug for the development of HCA and HCC. In fact, a few studies have reported that verteporfin treatment significantly inhibited HCC development (Gavini et al 2019 ; Quan et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our result suggested that verteporfin could be used as a preventive drug for the development of HCA and HCC. In fact, a few studies have reported that verteporfin treatment significantly inhibited HCC development (Gavini et al 2019 ; Quan et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In combination with erlotinib, VP reduced invasion, migration and sphere-forming ability. 637 Verteporfin (VP) Liver cancer Verteporfin-mediated inhibition of YAP/TAZ signaling significantly improved transcatheter arterial chemoembolization in transplanted hepatocellular carcinoma (HCC) 638 Verteporfin (VP) Gastric cancer VP disrupts YAP/TAZ-TEAD interaction to decrease the pool of gastric cancer stem cells. 639 Verteporfin (VP) Head and neck cancer (HNSCC) VP suppresses proliferation and metastasis by inhibiting YAP1.…”
Section: Applications In Biomedical Research and Targeted Therapymentioning
confidence: 99%
“…Moreover, this process could also be driven by YAP1-mediated survival expression [ 102 ]. Inhibition of the Hippo-YAP1 signaling using verteporfin (VP) in combination with transcatheter arterial chemoembolization (TACE), a commonly used therapeutic approach for unresectable HCC, allows reduced tumor burden and improved survival in a transplanted HCC mice model [ 103 ].…”
Section: Hippo Pathway and Other Digestive Malignanciesmentioning
confidence: 99%